La venue du malheur dans les livres des Rois et le livre de Jérémie - Gosse, Bernard (Biblische Notizen, 2012)
The coming of the misfortune is a theme of the books of the Kings about the kingdom of the North and then of the South. This theme is connected to the deuteronnomic theme of the hmqwm hzh. In the Book of Jeremy we have three successive redactions about this theme, first against Jerusalem, then every flesh and finally Babylon.